Promotion of Thai way of tourism after the coronavirus disease 2019 (COVID-19) situation - Phuripinisnant, Thanyaphat (MCU Haripunchai Review, 2022)
The past tourism situation in Thailand has generated enormous income into the country. As a result, tourism business has achieved the highest operating results, especially popular tourist destinations such as Chiang Mai, Phuket, Surat Thani, Chonburi, and Bangkok etc. However, Thai society is a society with secondary tourism that generates no less income for the country, such as Tai Lue Muang Mang and Muang Community in Phayao Province, Ban Lao Wiang Community in Uttaradit Province, Na Thon Community in Nakhon Phanom Province, Ban Chiang Community in Udon Thani Province, Ban Yuan Community and Nakhon Chantuk in Nakhon Ratchasima Province, and Nang Loeng Community in Bangkok, etc. These communities can create jobs and generate income for many local people without having to go to work in the provinces. The coronavirus disease 2019 (COVID-19) situation has made career and income disappear encountered obstacles. Moreover, there are many issues that may require a review of the preparation strategy after the situation has resolved. The strategy review is as follows: 1) developing mechanisms for building safety and confidence in trajectory tourism, 2) separation of accommodations such as portable tent or “homestays” or other things to have more distance from each other, 3) zoning and around visiting places to have smaller groups, 4) developing community knowledge along with the concept of community tourism development, and 5) modifying the online financial transaction system.